Stimuli-responsive properties of N-isopropylacrylamide-based ultrathin hydrogel films prepared by photo-cross-linking - Matsukuma, Daisuke (Langmuir : the ACS journal of surfaces and colloids, 2006)
To develop stimuli-responsive ultrathin polymer films on a solid substrate, a novel photo-cross-linkable polymer with both temperature- and pH-responsive properties was prepared. The photoreactive 4-aminobenzophenone (BP) was introduced onto the side groups of poly(N-isopropylaclylamide-co-2-carboxyisopropylaclylamide) [poly(NIPAAm-co-CIPAAm)]. This copolymer was designed for highly random sequences of comonomers. After the formation of spin-coated polymer films on a solid substrate, UV-light irradiation started the cross-linking reaction. The spin-coating processes and stability of the polymer films were quantitatively monitored by a quartz crystal microbalance (QCM), and the thickness was estimated using an atomic force microscope (AFM). These measurements confirmed the formation of a very plain polymer film, and the film thickness was precisely controlled by the concentration of the polymer solution used for spin coating. Moreover, the obtained films showed a high stability due to the cross-liking reaction and UV irradiation. Cyclic voltammetry using potassium ferricyanide revealed that the ions could permeate the photo-cross-linked ultrathin polymer films. The permeability of the ultrathin hydrogel films was dramatically changed by varying the pH and temperature of the aqueous media. These observations suggest that the preparation of isopropylacrylamide-based stimuli-responsive ultrathin hydrogel films is possible